Virotherapy of ovarian cancer with polymer-cloaked adenovirus retargeted to the epidermal growth factor receptor. - Morrison, J; Briggs, S; Green, N; Fisher, K; Subr, V; Ulbrich, K; Kehoe, S; Seymour, L (2008)
Adenovirus gene therapy for intraperitoneal (IP) cancer is limited in clinical trials by inefficient tumor cell transduction and development of peritoneal adhesions. We have shown previously that normal virus tropism can be ablated by physically shielding the virus surface with reactive hydrophilic polymers and that linkage of novel ligands enables virus "retargeting" through chosen receptors. To achieve tumor-selective infection, polymer-coated virus was retargeted using murine epidermal growth factor (mEGF). The resulting mEGF-polymer coated adenovirus lost its normal broad tropism and transduced cells selectively via the EGF receptor (EGFR). We assessed whether this approach could be used to target lytic "virotherapy" using wild-type adenovirus (Ad5WT) in a peritoneal xenograft model of human ovarian cancer. Oncolytic activity of Ad5WT was retained following polymer coating and mEGF-retargeting. Importantly, adhesion formation was markedly decreased compared with the unmodified virus, and no dose-limiting toxicities were observed following treatment with mEGF-retargeted polymer-coated virus. Restricting virus tropism by physical coating, coupled with tumor-selective retargeting promises to combine good anticancer efficacy with acceptable toxicity, enabling application of elevated virus doses leading to an improved therapeutic outcome.